Dysplasia in Inflammatory Bowel Diseases: Definition and Clinical Impact - Karel Geboes; Paul Rutgeerts (Canadian Journal of Gastroenterology)
Dysplasia is a morphological term that ethymologically means ‘malformation’. For the definition of inflammatory bowel disease-related dysplasia, the nature and origin of the malformation are stressed and the lesion is defined as an epithelial malformation that is unequivocally neoplastic but noninvasive. The use of a precise definition is necessary because of the clinical consequences related to the finding of dysplasia in IBD. The microscopic diagnosis of dysplasia, however, remains difficult. Clinically, it is important to make a proper differential diagnosis between polypoid IBD-related dysplasia and sporadic adenoma occurring in IBD, and between therapy-related ‘pseudodysplasia’ and genuine dysplasia. When dysplasia is diagnosed, a second opinion may be indicated because of the clinical consequences. Additional techniques to search for genetic defects associated with carcinogenesis can help to support the diagnosis. They can identify changes in DNA content and molecular changes resulting from defects of genes controlling cell proliferation and death or tissue structure. These changes can, however, be absent, appear early or late in the transition from normality toward dysplasia and cancer, or appear during repair. Positive findings indicate an increased cancer risk, but the magnitude of the risk remains to be defined. A positive diagnosis of genuine dysplasia necessitates clinical action – either follow-up of the patient or treatment. In practice, treatment means surgery because dysplasia can be a precursor and/or a marker of malignancy, except for sporadic adenomas, which can be removed locally.